Shear and Dynamic Compression Modulates the Inflammatory Phenotype of Human Monocytes in vitro - Fahy, Niamh; Menzel, Ursula; Alini, Mauro; Stoddart, Martin J. (Frontiers in Immunology, 2019)
Monocytes and their derived macrophages are found at the site of remodelling tissue, such as fracture hematoma, that is exposed to mechanical forces and have been previously implicated in the reparative response. However, the mechanoresponsive of monocytes and macrophages to skeletal tissue-associated mechanical forces and their subsequent contribution to skeletal repair remains unclear. The aim of this study was to investigate the potential of skeletal tissue-associated loading conditions to modulate human monocyte activation and phenotype. Primary human monocytes or the human monocyte reporter cell line, THP1-Blue, were encapsulated in agarose and exposed to a combination of shear and compressive loading for one hour a day for 3 consecutive days. Exposure of monocytes to mechanical loading conditions increased their pro-inflammatory gene and protein expression. Exposure of undifferentiated monocytes to mechanical loading conditions significantly upregulated gene expression levels of interleukin(IL)-6 and IL-8 compared to free swelling controls. Additionally, multiaxial loading of unstimulated monocytes resulted in increased protein secretion of TNF-α (17.1 ± 8.9 vs 8 ± 7.4 pg/ml) and MIP-1α (636.8 ± 471.1 vs 124.1 ± 40.1 pg/ml), as well as IL-13 (42.1 ± 19.8 vs 21.7 ± 13.6) compared monocytes cultured under free-swelling conditions. This modulatory effect was observed irrespective of previous activation with the M1/pro-inflammatory differentiation stimuli lipopolysaccharide & interferon-γ or the M2/anti-inflammatory differentiation factor interleukin-4. Furthermore, mechanical shear and compression were found to differentially regulate nitric oxide synthase 2 (NOS2) and IL-12B gene expression as well as inflammatory protein production by THP1-Blue monocytes. The findings of this study indicate that human monocytes are responsive to mechanical stimuli, with a modulatory effect of shear and compressive loading observed towards pro-inflammatory mediator production. This may play a role in healing pathways that are mechanically regulated. An in depth understanding of the impact of skeletal tissue-associated mechanical loading on monocyte behavior may identify novel targets to maximise inflammation-mediated repair mechanisms.